2005
DOI: 10.1007/s00436-005-1481-9
|View full text |Cite
|
Sign up to set email alerts
|

Red fox (Vulpes vulpes) cannibalistic behaviour and the prevalence of Trichinella britovi in NW Italian Alps

Abstract: Food habits of the red fox (Vulpes vulpes) were studied in the Aosta Valley region (NW Italian Alps) and were related to the prevalence of Trichinella infection in the red fox itself and in two Mustelid species (the stone marten (Martes foina) and the badger (Meles meles)). The search of Trichinella by the automatic digestion of muscles samples led us to determine a prevalence of 3.5+/-1.2% in red foxes, 7.9+/-4.3% in stone martens and 1.9+/-1.8% in badgers, with no significant differences among the species. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 23 publications
3
20
0
Order By: Relevance
“…The absence of Trichinella spp. in mentioned studies is in agreement with very low prevalence in the badgers reported by Torres et al (2001) in Spain (2.1%) or Remonti et al (2005) in Italy (1.9%). On the contrary, only a few cases of Trichinella infection have been reported for the pine martens (Martes martes) or stone martens (Martes folina), although their habitat of forming family groups and sharing the same sets implicate favorable management of Trichinella transmission (Woodroffe and Macdonald 1993).…”
Section: Trichinella Britovi Marten Badger Pcr Polandsupporting
confidence: 90%
See 1 more Smart Citation
“…The absence of Trichinella spp. in mentioned studies is in agreement with very low prevalence in the badgers reported by Torres et al (2001) in Spain (2.1%) or Remonti et al (2005) in Italy (1.9%). On the contrary, only a few cases of Trichinella infection have been reported for the pine martens (Martes martes) or stone martens (Martes folina), although their habitat of forming family groups and sharing the same sets implicate favorable management of Trichinella transmission (Woodroffe and Macdonald 1993).…”
Section: Trichinella Britovi Marten Badger Pcr Polandsupporting
confidence: 90%
“…The high prevalence among martens, suggests that these animals are important reservoir of the parasite in these countries. In other studies by Remonti et al (2005) and T. britovi larvae were present in 13.2% and 37.9% of examined martens, respectively. Additionally in Lithuania, two cases of infection in martens were classified as T. britovi, and in a third marten, a triple infection was noticed: T. britovi, T. nativa and T. spiralis (Malakauskas et al 2007).…”
Section: Trichinella Britovi Marten Badger Pcr Polandmentioning
confidence: 57%
“…Finally, previous records of Trichinella sp. in northern Italy mainly concerned carnivores from western regions (Di Matteo et al, 1991;Remonti et al, 2005). Therefore, the detection of Trichinella sp.…”
Section: Discussionmentioning
confidence: 99%
“…The aim of our study was to compare fox diets using analysis of stomach contents and faecal samples in the western Italian Alps, where the red fox has been reported to rely mainly on rodents, wild fruit, and ungulate carrion [20][21][22].…”
Section: Introductionmentioning
confidence: 99%